Pengaruh Pertumbuhan Ekonomi, Pembangunan Manusia, Kemiskinan dan Pengangguran terhadap Ketimpangan Distribusi Pendapatan: Studi di Provinsi Kepulauan Bangka Belitung Tahun 2005-2019 - Arkum, Darol; Amar, Hattami (Jurnal Bina Praja, 2022)
The income Distribution Inequality of Bangka Belitung Islands Province is the lowest nationally. This study aims to obtain more in-depth information regarding any variables or factors that affect the Inequality of Income Distribution in the Province of Bangka Belitung Islands. The type of research used associative quantitative research with Multiple Linear Regression and Simple Linear Regression models, as well as feasibility tests with classical assumption tests, Simultaneous and Partial hypothesis testing. The results of this study indicate that the factors affecting income distribution inequality in the Province of the Bangka Belitung Islands are economic growth, human development, poverty, and unemployment by 60.9 percent. Other factors influence the remaining 39.1 percent.Â Partially, economic growth has a positive and significant effect of 30 percent with a regression coefficient of 0.009. Human development has a negative and significant effect of 55.5 percent with a regression coefficient of -0.006, and poverty has a negative and insignificant effect of 25.8 percent with a regression coefficient of -0.004, unemployment has a negative and insignificant effect of 11.1 percent with a regression coefficient of -0.003. In conclusion, it turns out that the human development factor has a very large role in reducing the inequality in income distribution in the Province of the Bangka Belitung Islands. So, recommendations to the Provincial Government need to continue to improve Human Development by improving education, health, and people's purchasing power, as well as socializing the importance of Human Development in reducing the level of inequality in development outcomes to the Regency/ City Government in the Province of the Bangka Belitung Islands Province.